Publicism of the Volga Region about the Problems of Culture and Art During the Times of the First Russian Revolution - Brodovskaya, Lyudmila; Buravleva, Vera; Galimzyanova, Liliya; Fazliev, Aivaz (Journal of History Culture and Art Research, 2018)
The relevance of the studied problem is defined by that role which the theater and the press of the Volga region province of the beginning of the XX century played in formation of a social and political position of the population of the region. The article reveals the place and a role of the creative intellectuals in society and its relation to revolutionary events in the country through newspaper journalism, on the example of M. Gorky’s creativity. The research is purposed to show change of public consciousness in the province and the theater during revolution under the influence of various social and political forces this found the reflection in periodicals; and thus to promote formation of fuller picture of historical and cultural life of the country. Materials of article can be used in educational process, during creation of the generalizing works on history and cultural history of Russia, special courses, in educational work with children and youth, at adoption of administrative decisions in the welfare sphere.